2003
DOI: 10.1097/01.blo.0000093030.56370.d9
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Incision Total Knee Arthroplasty: Early Experience

Abstract: Total knee arthroplasty (TKA) has evolved during the past 30 years to a well-defined technical surgery with excellent results for as many as 20 years of followup. The concepts of exposure, ligament balancing, and joint alignment have been established clearly by Insall and others. In the early 1990s, Repicci introduced minimally invasive surgery for unicondylar knee arthroplasty. This approach suggested that less invasive surgery could accomplish similar results to those of standard unicondylar knee arthroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
181
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(189 citation statements)
references
References 6 publications
2
181
0
6
Order By: Relevance
“…The extensor mechanism suffers less damage and the patella is not everted in a MIS TKA, which would result in good patellar tracking and lower incidence of anterior knee pain. However, the literature shows only early recovery and less postoperative pain in patients who have had MIS TKAs [4,14,28], but does clarify the incidence of patellar maltracking or the development of anterior knee pain. Additionally, it is unclear whether the incidence of patellar maltracking or anterior knee pain differ with the MPP or MV approach in MIS TKAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensor mechanism suffers less damage and the patella is not everted in a MIS TKA, which would result in good patellar tracking and lower incidence of anterior knee pain. However, the literature shows only early recovery and less postoperative pain in patients who have had MIS TKAs [4,14,28], but does clarify the incidence of patellar maltracking or the development of anterior knee pain. Additionally, it is unclear whether the incidence of patellar maltracking or anterior knee pain differ with the MPP or MV approach in MIS TKAs.…”
Section: Discussionmentioning
confidence: 99%
“…It was believed to reduce hospitalization time [4,28], increase ROM [14,28], reduce pain [4,14], and more rapidly restore function [4]. In addition, if the quadriceps in the MPP approach is cut no more than 2 cm above the superior pole of the patella, the quadriceps recovers more rapidly [6,27].…”
mentioning
confidence: 99%
“…It offers the advantages of reduced intraoperative blood loss and pain, shorter hospital stay, and increased range of motion over more traditional arthroplasties. 23,24 Low-profile devices like the HemiCAP TM also preserve bone stock, allowing for subsequent modification. Unlike existing marketed devices, the HemiCAP TM also does not require replacement of the apposing tibial articular surface.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors such as Tria and Coon 15 and Berger et al 12 have demonstrated the benefits of minimally invasive surgery in knee arthroplasty, such as smaller surgical incision, shorter hospitalization time, less postoperative pain and earlier ambulation without requiring orthosis. Still concerning the preservation of extensor apparatus in knee arthroplasty, Silva et al 24 say that a stronger quadriceps strength is associated to better scores in functional assessments.…”
Section: Referencesmentioning
confidence: 99%